Depicting the 'Fighting Irish': Irish and Irish-American Representations of World War One in US Sheet Music Covers - Lauren Alex O'Hagan (Review of Irish Studies in Europe)
This paper offers the first in-depth exploration of the Irish and Irish-American experience of World War One through the lens of US sheet music covers, drawing upon a dataset from 1914 to 1919 collected from the Ward Irish Music Archives. By examining the stylistic and compositional choices on these covers, I identify four key themes: nostalgia and longing for Ireland, farewells to Ireland, loyalty to Britain (and later to the United States) and idealised Irish qualities. These covers combined various images and stereotypes about Ireland, which was instrumental in shaping public perceptions of Irish and Irish-American roles in the war. Specifically, they constructed an idealised vision of the wartime experience, omitting violence, masking Ireland’s internal divisions and presenting the country as a unified homeland whose citizens fully backed Britain, and later the US, in their military efforts. This portrayal sought to address Irish-American anxieties regarding patriotism and loyalty amid scrutiny of their identities. The findings prompt a re-evaluation of seemingly mundane objects in mass-market media, revealing how they can provide fresh insights into race, nationhood and identity. They also encourage readers to consider whether the sheet music served primarily as propaganda, a commercial venture, or a complex blend of both, adding nuance to our understanding of World War One experiences from Irish, Irish-American and visual culture perspectives.